Management accounting change: a case study of balanced scorecard implementation in a Portuguese service company - Pimentel, L.; Major, M. J. (Contabilidade e Gestão: Portuguese Journal of Accounting and Management, 2010)
This paper presents a longitudinal case study of management accounting change (MA) in a Portuguese service company operating within the information technology business, which has implemented a Balanced scorecard (BSC). BSC implementation turned out to be problematic. It took too long and faced several dificulties and obstacles. Drawing upon Kasurinen's revised model of accounting change, the factors that created a potential for change (motivators, facilitators and catalysts) and the events that seek to explain how the process of change evolved (momentum and leadership) are identified. Furthermore, Kasurinen's barriers to change (confusers, frustraters and delayers) have been recognised in the study. This investigation demonstrates how Kasurinen's (2002) framework can help researchers to understand the reasons and explanations as to why change occurs in organizations and the process by which MA changes.